COVID-19: Do DNA / RNA vaccines integrate into the genome? - Pacheco, Thyago José Arruda (2021)
The new coronavirus pandemic brought the need for researchers to work tirelessly in the search for therapies or vaccines that would allow control of the spread of the virus around the world. Fortunately there are two RNA vaccines against COVID-19 that have finished clinical tests and are approved in some countries. They are the first third generation vaccines approved in history and in time record. But still have some concerns about safety of DNA/RNA vaccines. Here we bring a discussion about safety of DNA/RNA: can these vaccines be integrated to the genome? In fact, DNA vaccines have an infinite chance to integrate in the cell's genome, but this infinite chance is equal zero when used with RNA-based vaccines. The vaccines based on nucleic acid (DNA and RNA) have been corresponding in advantages, becoming promising alternatives to guarantee the immunization of the new coronavirus.